2017
DOI: 10.14730/aaps.2017.23.2.57
|View full text |Cite
|
Sign up to set email alerts
|

Will a Fibrin Sealant be Effective as a Seroma Reductant and a Hemostatic Agent in Breast Reconstruction Using a Latissimus Dorsi Flap?

Abstract: BackgroundThe latissimus dorsi (LD) flap is widely used in breast cancer reconstruction, but donor-site morbidity is one of the major limitations of this surgery. Donor-site seroma is the most common complication. To prevent seroma formation, we consider the use of a fibrin sealant (FS) because of its hemostatic and sealing effects. In this study, we investigate the effect of a FS on seroma prevention and as a hemostatic agent at the LD donor site. Methods A retrospective study was conducted from 2011 to 2015.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…16,17 Similarly, Lee et al conducted a retrospective cohort study demonstrating that fibrin sealant was neither effective as a hemostatic agent nor as a seroma reductant. 14 Among the individual cohorts analyzed in our study, Weinrach et al demonstrated a significant reduction in seroma formation following fibrin glue application. 18 Similarly, Ali et al and Hivelin et al found that fibrin glue led to a significant reduction in the duration of drainage and earlier drain removal following reconstruction.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…16,17 Similarly, Lee et al conducted a retrospective cohort study demonstrating that fibrin sealant was neither effective as a hemostatic agent nor as a seroma reductant. 14 Among the individual cohorts analyzed in our study, Weinrach et al demonstrated a significant reduction in seroma formation following fibrin glue application. 18 Similarly, Ali et al and Hivelin et al found that fibrin glue led to a significant reduction in the duration of drainage and earlier drain removal following reconstruction.…”
Section: Discussionmentioning
confidence: 58%
“…16 17 Similarly, Lee et al conducted a retrospective cohort study demonstrating that fibrin sealant was neither effective as a hemostatic agent nor as a seroma reductant. 14…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation